Exploration of Coal Deposits - J L. Edwards; P Hatherly; J Lea (The Australasian Institute of Mining and Metallurgy, 2009)
Coal exploration has traditionally involved the acquisition of data to enable a resource to be quantified and qualified to the extent that its economic potential can be determined. This process commonly relied on: drilling to determine the depth and thickness of coal seams, broad characterisation of the overburden and interburden, and to provide cores for coal quality analyses; basic wireline logging to cross-check the depth and thickness of coal seams and provide some indication of rock mass strength; and basic surface geophysics and remote sensing to identify major geological structures. In recent years, the adoption of the JORC Code as a basis for the reporting of resources and reserves has placed a greater emphasis on the need for detailed, reproducible data sets that not only satisfy the traditional requirements of mine planners, but also satisfy the governance requirements of corporate and financial institutions. Similarly, the development of sophisticated numerical modelling techniques for use in both open cut and underground mine design, has seen a greater demand for precise geotechnical data, in situ stress characterisation and hydrological information as routine input to the design process. These requirements, coupled with the prevailing trend toward high capital, relatively inflexible mining techniques less tolerant of geological surprises, and the need for consideration of environmental issues such as groundwater impacts and surface subsidence, requires that modern exploration programs be multifaceted, and designed to commence capturing data relevant to ædownstream issuesÆ even during the initial phases of exploration planning.